2018
DOI: 10.1016/j.biochi.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the beta 2 agonist formoterol on atrophy signaling, autophagy, and muscle phenotype in respiratory and limb muscles of rats with cancer-induced cachexia

Abstract: Muscle mass loss and wasting are characteristic features of patients with chronic conditions including cancer. Beta-adrenoceptors attenuate muscle wasting. We hypothesized that specific muscle atrophy signaling pathways and altered metabolism may be attenuated in cancer cachectic animals receiving treatment with the beta agonist formoterol. In diaphragm and gastrocnemius of tumor-bearing rats (intraperitoneal inoculum, 10 AH-130 Yoshida ascites hepatoma cells, 7-day study period) with and without treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 63 publications
(142 reference statements)
5
43
0
Order By: Relevance
“…autophagy flux, supporting the idea that direct blockade of protein degradation should not be pursued. Few studies tried to uncover the mechanism underlying formoterol effect on muscle proteolysis in both healthy [24] and wasting (cancer-related) conditions [25,26] Consistently, survival of tumor-bearing mice is not impaired when autophagy is induced in the skeletal muscle by TP53INP2 overexpression, at least in the experimental settings adopted in this study, despite muscle protein depletion is exacerbated. Previous data suggested that TP53INP2 repression was part of an adaptive mechanism aimed at preserving muscle mass upon insulin deficiency or insulin resistance [10,17].…”
Section: Accepted Manuscriptsupporting
confidence: 51%
“…autophagy flux, supporting the idea that direct blockade of protein degradation should not be pursued. Few studies tried to uncover the mechanism underlying formoterol effect on muscle proteolysis in both healthy [24] and wasting (cancer-related) conditions [25,26] Consistently, survival of tumor-bearing mice is not impaired when autophagy is induced in the skeletal muscle by TP53INP2 overexpression, at least in the experimental settings adopted in this study, despite muscle protein depletion is exacerbated. Previous data suggested that TP53INP2 repression was part of an adaptive mechanism aimed at preserving muscle mass upon insulin deficiency or insulin resistance [10,17].…”
Section: Accepted Manuscriptsupporting
confidence: 51%
“…An adaptive response to oxidative stress is also induced by formoterol, a b2-adrenoceptor-selective agonist. Several studies report the beneficial effects of this compound in reverting cancer-induced muscle wasting in both animal models and cancer patients by triggering protein metabolism toward synthesis and reducing inflammation (53,92,114,136,137). Along with the anabolic/anticatabolic effects, formoterol also prevents the increase of oxidized proteins and MDA/HNE-protein adducts in the skeletal muscle of Yoshida AH-130-bearing rats (115).…”
Section: Fig 5 Exercise Modu-mentioning
confidence: 99%
“…Busquets et al . observed a ß 2 ‐adrenergic agonist to reduce the mRNA content of ubiquitin and proteasome subunits in gastrocnemius muscle (GAS), thus contributing to the observed anti‐wasting effects …”
Section: Introductionmentioning
confidence: 99%